MORPHOLOGY AND LANGUAGE ERRORS ANALYSIS SYNTACTIC OF CLASS 7 STUDENTS' DESCRIPTION COOKS SMP PGRI JATIUWUNG TANGERANG 2022/2023 - Darnisa, Desy Rita; Kamiri, Kamiri; Goziyah, Goziyah (Jurnal Dinamika UMT, 2023)
After conducting a content analysis of the January 2023 episode of the  Mata Najwa talk show, which consisted of three talk show titles, namely  Deliberation Tuntun Sambo Until Candidates for the PSSI Chairperson, the  authors drew several conclusions. The speech contained in the January 2023  episode of the Mata Najwa talk show, entitled Deliberation on guiding Sambo to  PSSI chairman candidates, contained the use of elements of politeness in the  Leech Politeness Principle, for example in the use of the principle of politeness,  namely an agreement between the speaker and the hearer and the maxim of  humility, because the program Najwa's eyes are speakers and speech partners who  have a good education, so they pay great attention to the principle of politeness in  speaking